Advancing Breast Cancer Therapeutics: Targeted Gene Delivery Systems Unveiling the Potential of Estrogen Receptor-Targeting Ligands - Lee, Jung Ro; Kim, Young-Min; Kim, Eun-Ji; Jang, Mi-Kyeong; Park, Seong-Cheol (Biomaterials research, 2024)
Although curcumin has been well known as a phytochemical drug that inhibits tumor promotion by modulating multiple molecular targets, its potential was not reported as a targeting ligand in the field of drug delivery system. Here, we aimed to assess the tumor-targeting efficiency of curcumin and its derivatives such as phenylalanine, cinnamic acid, coumaric acid, and ferulic acid. Curcumin exhibited a high affinity for estrogen receptors through a pull-down assay using the membrane proteins of MCF-7, a breast cancer cell line, followed by designation of a polymer-based gene therapy system. As a basic backbone for gene binding, dextran grafted with branched polyethylenimine was synthesized, and curcumin and its derivatives were linked to lysine dendrimers. In vitro and in vivo antitumor effects were evaluated using plasmid DNA expressing anti- bcl-2 short hairpin RNA. All synthesized gene carriers showed excellent DNA binding, protective effects against nuclease, and gene transfection efficiency in MCF-7 and SKBr3 breast cancer cells. Preincubation with curcumin or 17α-estradiol resulted in a marked dose-dependent decrease in gene transfer efficiency and suggested targeting specificity of curcumin. Our study indicates the potential of curcumin and its derivatives as novel targeting ligands for tumor cells and tissues.